Angle-dependent vortex structure in a high anisotropy superconductor - Pratt, F; Marshall, I; Blundell, S; Drew, A; Lee, S; Ogrin, F; Toyota, N; Watanabe, I (2003)
Angle-dependent muon spin rotation measurements have been made on the organic superconductor kappa-(BEDT-TTF)(2)Cu(SCN)(2). Oscillations are observed in the width of the internal field distribution, which are periodic in the perpendicular component of the applied magnetic field, B-z = B cos theta, with a uniform period over a range of angles and fields. These oscillations are superimposed on the standard cos theta scaling expected for the width in a highly anisotropic superconductor. The oscillation period is of order 2 mT and the amplitude is particularly strong at fields comparable with the period. The origin of this novel phenomenon is discussed in terms of the low field instabilities of tilted vortices in this highly anisotropic superconductor. (C) 2002 Elsevier Science B.V. All rights reserved.